Changes of blood glucose and lipid metabolism in breast cancer patients with cancer-related fatigue during chemotherapy: a cross-sectional survey - Liu, Yaqing; Huang, Zhaoyang; Lin, Qingzhong; Gao, Wensi; Yang, Sujuan; Chen, Mei; Yang, Jinxia (Journal of Medical Biochemistry, 2025)
Objective: To cross-sectionally investigate the correlation of cancer-related fatigue (CRF) with quality of life (QoL) and physical fitness of breast carcinoma (BC) patients during chemotherapy, so as to provide reference and guidance for the future clinical development of better medical services for BC patients during chemotherapy. Methods: From February 2023 to July 2023, 400 BC patients treated at the Breast Surgery Department of the Fujian Cancer Hospital were selected as the research subjects. Physical fitness-associated indicators were investigated, including body composition, muscle function, cardiopulmonary function, and the scores of CRF Scale, QoL Questionnaire, and Exercise Self-Efficacy Scale were investigated. Further analysis was conducted on the differences in physical fitness between neoadjuvant chemotherapy (NACT) and postoperative adjuvant chemotherapy (POAC), as well as between patients with and without exercise habits. Results: Electrocardiogram showed that 244 (61.00%) had normal heart rhythm, but 29 (7.25%) still developed abnormal cardiac function. A greater number of patients receiving NACT showed low HDL-C than those undergoing POAC (P<0.05). In patients with exercise habits, there was a larger proportion of reduced hemoglobin (Hb) compared with those without exercise habits, with higher QoL questionnaire scores (P<0.05). Conclusions: CRF during chemotherapy was evident in BC patients. Among them, patients undergoing NACT show lower HDL-C levels, while those with exercise habits have lower Hb and higher QoL scores.